The analysis of efficiency of use of mobile mammographs in territorial subjects of the Russian Federation - D. A. Kaprin (Опухоли женской репродуктивной системы, 2025)
Aim. To study equipment of health care systems of territorial subjects of the Russian Federation mobile mammography caravans and to estimate results of their work.Materials and methods. Sources of information on volumes of work of mobile mammography caravans – a form of federal statistical observation No. 30 on each of territorial subjects of the Russian Federation. For assessment of dependences between variables the regression analysis and data from a form of federal statistical observation No. 7 for 2022 was used.Results. Indicators of load of one mammography installation averaged in 2022 49.9 ± 44.6 departures a year and fluctuated in different territorial subjects of the Russian Federation from 3 to 130 departures in a year. The regression analysis showed that only 4.3 % of a variation of an indicator “the share of the cases of a breast cancer revealed actively” depends volumes of activity of mobile mammographs. At the same time the regional variation of an indicator “number of the accepted patients at departures” does not depend neither on population density, nor on volumes of medical care in policlinics, and statistical bonds between a share of the cases of a breast cancer revealed actively and number of the patients accepted at departures of mobile mammographs no.Conclusion. It is necessary to call into question efficiency of total inspection of the population with use of mobile mammography and also to personalize selection of the contingents for mammography on the basis of assessment of polygenic risk and the family anamnesis.